EMPLOYEE MOTIVATION, JOB SATISFACTION, AND EMPLOYEE PERFORMANCE: A LITERATURE REVIEW - Hidayat, Imam; Supardi, Endi; Anwar, Alvis; Anggiani, Sarfilianty (Dinasti Publisher, 2022)
The purpose of this paper is to provide a structured literature review on the constructs of employee motivation, job satisfaction, employee performance, and empirical evidence on the relationship between motivation, job satisfaction, and performance. 20 (twenty) papers published during 2017-2021 that investigates employee motivation, job satisfaction, employee performance, and the relationship between employee motivation, job satisfaction, and employee performance were reviewed. The results of the review show that employee motivation and job satisfaction have positive and significant effect on employee performance or in other word employee motivation and job satisfaction are the determinants of employee performance.